Research on Resource Scheduling of Computing Power Network Based on Deep Q-Network Algorithm - Wang, Zhijun; Zhou, Jingbo (2024 3rd International Conference on Cloud Computing, Big Data Application and Software Engineering (CBASE), 2024)
The resource scheduling of computing power networks is a complex project, and the scheduling strategies used will directly affect the efficiency of subsequent processing of computing tasks. This article focuses on the resource scheduling problem of computing power networks, using the DQN algorithm in deep reinforcement learning to optimize resource utilization, resource mobilization rate, and reduce task loss rate, providing a solution.